From science to policy: How European HBM indicators help to answer policy questions related to phthalates and DINCH exposure - Gerofke, Antje; David, Madlen; Schmidt, Phillipp; Vicente, Joana Lobo; Buekers, Jurgen; Gilles, Liese; Colles, Ann; Bessems, Jos; Bastiaensen, Michiel; Covaci, Adrian; Den Hond, Elly; Koppen, Gudrun; et al. (International journal of hygiene and environmental health, 2023)
Within the European Human Biomonitoring (HBM) Initiative HBM4EU we derived HBM indicators that were designed to help answering key policy questions and support chemical policies. The result indicators convey information on chemicals exposure of different age groups, sexes, geographical regions and time points by comparing median exposure values. If differences are observed for one group or the other, policy measures or risk management options can be implemented. Impact indicators support health risk assessment by comparing exposure values with health-based guidance values, such as human biomonitoring guidance values (HBM-GVs). In general, the indicators should be designed to translate complex scientific information into short and clear messages and make it accessible to policy makers but also to a broader audience such as stakeholders (e.g. NGO's), other scientists and the general public. Based on harmonized data from the HBM4EU Aligned Studies (2014-2021), the usefulness of our indicators was demonstrated for the age group children (6-11 years), using two case examples: one phthalate (Diisobutyl phthalate: DiBP) and one non-phthalate substitute (Di-isononyl cyclohexane-1,2- dicarboxylate: DINCH). For the comparison of age groups, these were compared to data for teenagers (12-18 years), and time periods were compared using data from the DEMOCOPHES project (2011-2012). Our result indicators proved to be suitable for demonstrating the effectiveness of policy measures for DiBP and the need of continuous monitoring for DINCH. They showed similar exposure for boys and girls, indicating that there is no need for gender focused interventions and/or no indication of sex-specific exposure patterns. They created a basis for a targeted approach by highlighting relevant geographical differences in internal exposure. An adequate data basis is essential for revealing differences for all indicators. This was particularly evident in our studies on the indicators on age differences. The impact indicator revealed that health risks based on exposure to DiBP cannot be excluded. This is an indication or flag for risk managers and policy makers that exposure to DiBP still is a relevant health issue. HBM indicators derived within HBM4EU are a valuable and important complement to existing indicator lists in the context of environment and health. Their applicability, current shortcomings and solution strategies are outlined.
Keywords: kyseliny ftalové; Male; Policy; Phthalic Acids; Phthalates; DINCH; Adolescent; Child; kyseliny karboxylové; dítě; Biological Monitoring; Science-policy uptake; mužské pohlaví; Human biomonitoring (HBM); mladiství; postup; lidé; biologický monitoring; ženské pohlaví; Humans; indicator; Carboxylic Acids; Female; HBM4EU